1984
DOI: 10.1111/j.1365-2044.1984.tb07240.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the Dinamap 845

Abstract: SummaryThe accuracy of the Dinamap 845 automatic blood pressure recorder was assessed by comparing its own indirect determinations of blood pressure with direct intra-arterial recordings. It was found that in the majority of cases it was capable of producing reliable trend information during anaesthesia. The instrument may not be able to interpret pressure signals from a patient with a severe dysrhythmia. It is probably an unsuitable monitor for use with very rapidly acting drugs such as sodium nitroprusside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…In this way both the absolute BP values and the CW/ArmC ratios are taken into consideration. In agreement with Hutton et al [8], we propose to correct electronically the deviations of regression lines from the line of equality. In addition as far as infants are concerned, a programme for different cuff ratios should be introduced.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this way both the absolute BP values and the CW/ArmC ratios are taken into consideration. In agreement with Hutton et al [8], we propose to correct electronically the deviations of regression lines from the line of equality. In addition as far as infants are concerned, a programme for different cuff ratios should be introduced.…”
Section: Discussionsupporting
confidence: 75%
“…Sch6ber, Kinderkrankenhaus an der Lachnerstraf3e, Lachnerstrage 39, D-8000 Mtinchen 2, Federal Republic of Germany Abbreviations: BP = blood pressure; BPM = blood pressure measurements; CW/ArmC = cuff width to arm circumference ratio; DAP = diastolic arterial pressure; MAP = mean arterial pressure; SAP = systolic arterial pressure; ME = mean error; SD = standard deviation also been used for BP monitoring during anaesthesia [5,9,18,19,21,25,28]. Some investigators found a good correlation between Dinamap and direct BPM [2,3,5,8,9,11,15,16,28], but most of these studies were performed on anaesthetised patients [2,28], in infants during heart catheterisation [3,4], or in groups of neonates and low birth weight infants [5,9,16]. There have been relatively few investigations involving the use of Dinamap for post-operative BPM in infants after heart surgery [19,25].…”
Section: Introductionmentioning
confidence: 96%
“…Oscillometric devices are widely used for this purpose and may give accurate assessment of mean arterial pressure, but are often inaccurate for registering systolic and diastolic pressure. 110,111 Blood pressure values obtained in acute care settings are unlikely to be useful for decisions on chronic hypertension management, 112 because of inadequate patient preparation, faulty equipment, 82 and the impact of the acute illness on blood pressure. Still, high readings recorded in the emergency room do predict hypertension on subsequent clinic visits, to some extent, 113 and warrant follow-up.…”
Section: Blood Pressure Measurement In Other Settingsmentioning
confidence: 99%
“…For this purpose the CM5 configuration is preferable to other single lead systems. Arterial pressure may be monitored non-invasively in those patients undergoing minor surgical procedures, and the newer automatic systems provide more consistent and repeatable measurements than manual techniques (Hutton, Dye and Prys-Roberts, 1984). For major surgery, the advantages of direct arterial pressure monitoring far outweigh any minor disadvantages, and the method provides beat-by-beat information on the cardiovascular system.…”
Section: General Anaesthesiamentioning
confidence: 99%